Intergovernmental or fully independent? Designing a scientific panel on evidence for action against antimicrobial resistance. - Arne Ruckert; Steven J Hoffman; Julia Bishop; Susan Rogers Van Katwyk; Patrick Fafard; Mathieu J P Poirier (PLOS Global Public Health)
Effective global action against antimicrobial resistance (AMR) relies on the successful synthesis and translation of rigorous scientific evidence into policy and practice. Despite a call in 2019 by the Interagency Coordination Group on AMR to establish a policy-science interface, and the reaffirmation to establish a scientific panel in the 2024 Political Declaration on Antimicrobial Resistance, no authoritative entity currently exists that synthesizes the scientific evidence on AMR and outlines policy options based on the best scientific insight. A Scientific Panel on Evidence for Action against AMR (SPEA) could address this gap, as well as contribute to additional governance gaps in the space of AMR, by facilitating better global coordination and cooperation; establishing real-time evidence to guide policy actions; and monitoring progress towards any globally agreed upon AMR goals and targets. In this essay, we argue that SPEA has the potential to fulfill several governance functions, and we explore two design options for such a scientific panel to promote equitable and evidence-informed policy implementation. We first reflect on how the successes and failures of the Intergovernmental Panel on Climate Change (IPCC) should inform the SPEA. Building on these lessons, we then highlight the key functions of the SPEA, before proposing two models for how it could function in the context of the existing global governance of AMR. Finally, we reflect on the challenges inherent to each proposed governance model. The recent reaffirmation by the United Nations General Assembly to establish a scientific panel in the area of AMR represents a critical opportunity to enhance global AMR governance, promote evidence-based policy implementation, and foster international cooperation in combatting AMR.